Pengaruh Komunikasi, Profesionalisme, dan Komitmen Organisasi Terhadap Semangat Kerja Pegawai pada Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Bima - Zainul Arifin; Kartin Aprianti; Khairul Amar (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to determine and analyze the influence of communication, professionalism, and organizational commitment on employee morale at the Public Works and Spatial Planning Agency of Bima Regency. This type of research is associative research. The research instrument uses a questionnaire with a Likert scale. The population in this study were all employees at the Public Works and Spatial Planning Agency of Bima Regency, totaling 201 people. The sample in this study were employees with the status of Civil Servants (PNS) and Government Employees with Work Agreements (PPPK) totaling 127 people, which were determined by purposive sampling technique, namely a sampling technique with certain considerations. Data collection techniques in this study were observation, interviews, questionnaires, and literature studies. Data analysis techniques used include validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, multiple correlation coefficients, t tests, and F tests. The results of the study indicate that partially communication and professionalism have a significant effect on employee morale, while organizational commitment has no significant effect. Simultaneously, communication, professionalism, and organizational commitment have a significant influence on employee work enthusiasm at the Public Works and Spatial Planning Agency of Bima Regency, with a contribution of 54.8% (Adjusted R Square), while the rest is influenced by other factors not examined in this study.